CSR: An Analysis with Respect to Companies and Beneficiary Perspective - Someshwari, Mrs.; P., Dr. Laxmana (International Journal of Scientific Research and Management (IJSRM), 2022)
Despite a plethora of studies on the link between corporate social responsibility and financial performance, the literature remains inconclusive. In this study, the relationship between corporate social responsibility and financial performance is examined in the context of India. The Study is focus on 9 Steel and Cement Industries and 435 Beneficiaries of Kalayaan Karnataka Region of Karnataka State, India. The findings of this study provide valuable insight for management in terms of integrating CSR with the organization's strategic goal and renovating their corporate philosophy from a profit-driven to a socially responsible approach.